IN MEMORIAM - Professor Emeritus Constantin Crăciun (15 September 1937 – 25 November 2016) - BANCIU, Horia L. (Studia Universitatis Babeș-Bolyai Biologia, 2017)
CONSTANTIN CRĂCIUN was born on September 15, 1937, in Pîrscoveni (Olt County, former Romanați County), Romania. Teodor Crăciun, the father of Constantin, graduated Philosophy and Theology at the University of Bucharest and became a devoted priest. He married Eva Cunescu, the daughter of a Moldavian boyar. Tragically, Eva Crăciun passed away while all her four children were very young (Constantin himself being only 3-years-old). Following this suffering moment, Teodor Crăciun moved with his family to Corabia where he was appointed as bishop. Constantin went on a deprived childhood and teenage, graduating the secondary school (Corabia), and the Technical High School for Topography (Bucharest, 1957). Constantin was afterwards appointed a job in Transylvania (Bihor County). At that time, he could not enroll in academic studies because of his politically ‘unhealthy’ ascendance, by the communist standards. Soon, however, Constantin was formally adopted by the family that hosted him in Batar village (Bihor County). It was a crucial moment in Constantin’s fate, as he was now ‘eligible’ to become a student at the Faculty of Biology (Babeş-Bolyai University of Cluj, 1961-1966).